A Combination of Curcuma longa and Diazepam Attenuates Seizures and Subsequent Hippocampal Neurodegeneration - Nascimento, Chirlene Pinheiro; Ferreira, Luan Oliveira; Silva, Alex Luiz Menezes da; Silva, Ana Beatriz Nardelli da; Rodrigues, Joao Cleiton Martins; Teixeira, Leonan Lima; Azevedo, Julianne Elba Cunha; Araujo, Daniella Bastos de; Hamoy, Akira Otake; Gonçalves, Beatriz Holanda; Coelho, Brenda Hosana De Oliveira; Lopes, Dielly Catrina Favacho; et al. (Frontiers in Cellular Neuroscience, 2022)
Epilepsy is one of the most common neurological disorders, which occurs due to instability in the inhibitory and excitatory synaptic transmission in the brain. However, many patients develop resistance to the available drugs, which results in cell degeneration caused by inadequate control of the seizures. Cucurmin, Curcuma longa, is known to be effective for the treatment of organic disorders, and may prevent seizures, reduce oxidative stress, and decrease brain damage. Given this, the present study evaluated the antiepileptic effects of C. longa in comparison with both diazepam and the combined application of these two substances, in terms of their effects on brain activity and potential histopathological changes in the hippocampus. The study used male Wistar rats (age: 10–12 weeks; weight: 260±20 g), which they were pretreated for 4 days with either saline, C. longa, diazepam or C. longa + diazepam, and on day 5, pentylenetetrazol (PTZ) was administered to induce seizure. In the C. longa group, a significant increase was observed in the latency of the onset of seizure-related behavior. Surprisingly, however, the combined treatment resulted in the best control of the seizure-related behavior, with the greatest latency of the onset of spasms and isolated clonic seizures. This group also obtained the best results in the electroencephalographic trace and seizure control, with a reduction in the frequency and amplitude of the spike-waves. In the saline group, PTZ reduced significantly the number of cells present in the CA1 and CA3 regions of the hippocampus, while the combined treatment obtained the best results in terms of the preservation of the neuron-like cells. These findings indicate that C. longa may contribute to the control of both seizures and the cell damage induced by PTZ, and that its association with diazepam may be a potentially effective option for the treatment of epilepsy in the future.